Comparison of contralateral oblique view with the lateral view for fluoroscopic-guided cervical epidural steroid injection: a randomized clinical trial. Issue 3 (1st December 2021) - Sim, Ji-Hoon; Kwon, Hyun-Jung; Kim, Chan-Sik; Kim, Eun Ha; Kim, Doo-Hwan; Choi, Seong-Soo; Shin, Jin-Woo
Abstract : Background: Cervical epidural steroid injection is associated with rare but potentially catastrophic complications. The contralateral oblique (CLO) view may be a safe and feasible alternative to the lateral (LAT) view for fluoroscopic-guided cervical epidural steroid injection. However, evidence for the clinical usefulness of the CLO view for cervical epidural steroid injection is lacking. We assessed the clinical usefulness of the CLO view for cervical epidural steroid injection in managing cervical herniated intervertebral discs. Methods: Patients were randomly assigned to receive fluoroscopic-guided cervical epidural steroid injection under LAT view or CLO view at 50±5° degrees groups. The primary outcome was the needling time comparison between the two groups. Secondary outcomes were comparison of first-attempt success rate, needle tip visualization and location, total number of needle passes, final success rate, crossover success rate and false-positive/negative loss of resistance. Complications and radiation dose were also compared. Results: The needling time significantly decreased in the CLO than in the LAT group. The first-attempt success rate was significantly higher in the CLO compared with the LAT group. The needle tip was clearly visualized (p<0.001) and located more often on (or just anterior to) the ventral interlaminar line (p<0.001) in the CLO than in the LAT group. There were significantly fewer needle passes (p=0.019) in the CLO than in the LAT group. There were no significant differences in the final success, crossover success, false-positive/negative loss of resistance or radiation dose between the groups. Two (5.9%) cases in the LAT group experienced complications. Conclusion: The CLO view may be recommended for fluoroscopic-guided cervical epidural steroid injection, considering its better clinical usefulness over the LAT view.